The Arab-Israeli conflict - Schulze, Kirsten E. (Routledge, Taylor & Francis Group, 2017)
"Analyzes the Arab-Israeli conflict, exploring the particular dynamics of this conflict and the numerous attempts at its resolution"--Provided by the publisher.